γ-Alumina Doped Alginate Gel for Cell Immobilization in Fermentation Processes - Jirawan Mongkolkajit; Jiranan Pullsirisombat; Seeroong Prichanont; Veerapat Tantayakom; Phatthanon Prasitchoke; Muenduen Phisalaphong (ASEAN Journal of Chemical Engineering, 2010)
γ-Alumina (γ-Al2O3) doped alginate gel (AEC) was developed as a cell carrier in fermentation processes of Saccharomyces cerevisiae M.30 for ethanol production and Clostridium butyricum DSM 5431 for 1,3-propanediol production. In a single batch system of ethanol fermentation, the final ethanol concentration of suspended cell (SC), immobilized cell on γ-Al2O3 (AC) and AEC cultures were 82.4, 77.1 and 74.6 g/l, respectively. In 4-cycle repeated batch fermentation, the AEC culture demonstrated a good potential of reusability. Its ethanol production and conversion yield of the 1st, 2nd and 3rd repeated batch were comparable to those of the SC and AC cultures with the immobilization yield of 86%. AEC was also found to be effective for the cell immobilization of C. butyricum with the immobilization yield of 83%. However, the strong inhibition effect of cell-γ-Al2O3 immobilization towards 1,3-propanediol production was observed. Moreover, 1, 3-propanediol fermentation stability in the SC, AC and AEC systems tended to be lowered during the repeated batch fermentation. Interfering of positive charge of γ-Al2O3 on the cell membrane was thought to be the cause of the inactivity of C. butyricum DSM 5431 in 1,3-propanediol production.